The Development of Student Worksheet to Enhance Students’ Mathematical Understanding on Two Variable Linear Equation System Topic - Dallyono, Ruswan; Hidayat, Wahyu; Kurniasari, Yeni; Fitriani, Nelly (IKIP Siliwangi, 2025)
Student worksheets play a crucial role in mathematics education by providing a structured framework for exploring concepts, practicing exercises, and achieving learning goals. However, understanding slope, intercepts, and graphing in linear equations with two variables (LETV) remains a common challenge for many students. Therefore, this study aims to develop a student worksheet for linear equations with two variables to enhance students’ comprehension in that specific area of mathematics for junior high school students based on their difficulties in solving problems on linear equations with two variables and to identify such difficulties based on articles written by 20 scholars published in Sinta-accredited journals. This qualitative study used text data from 20 nationally Sinta-accredited peer-reviewed mathematics education journals that presented articles about the challenges or difficulties of this topic as experienced by students. The data were analyzed through an SLR method by identifying the patterns of students’ difficulties or challenges and by analyzing how the student worksheet will handle such problems as reported in journal articles. This study also reveals that students’ challenges in studying this topic of maths involve conceptual misunderstandings, procedural errors, graphical interpretation issues, lack of real-world application, lack of creativity, lack of ability in writing mathematical representations, difficulty in understanding word or story problems, lack of mathematical process skills, and recklessness.